Endurance training and sprint performance in elite junior cross-country skiers - Sandbakk, O.; Welde, B.; Holmberg, H. C. (The Journal of Strength and Conditioning Research, 2011)
The purpose of the present study was to investigate the relationship between aerobic characteristics and sprint skiing performance, and the effects of high-intensity endurance training on sprint skiing performance and aerobic characteristics. Ten male and 5 female elite junior cross-country skiers performed an 8-week intervention training period. The intervention group (IG, n = 7) increased the volume of high-intensity endurance training performed in level terrain, whereas the control group (CG, n = 8) continued their baseline training. Before and after the intervention period, the skiers were tested for 1.5-km time-trial performance on roller skis outdoors in the skating technique. Maximal oxygen uptake (Vo2max) and oxygen uptake at the ventilatory threshold (Vo2VT) were measured during treadmill running. Vo2max and Vo2VT were closely related to sprint performance (r = ~0.75, both p < 0.008). The IG improved sprint performance, Vo2max, and Vo2VT from pre to posttesting and improved sprint performance and Vo2VT when compared to the CG (all p < 0.01). This study shows a close relationship between aerobic power and sprint performance in cross-country skiing and highlights the positive effects of high-intensity endurance training in level terrain.